2020
DOI: 10.1155/2020/6598434
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicinal Products fromPassiflorafor Anxiety: An Unexploited Potential

Abstract: Herbal medicines containing Passiflora species have been widely used to treat anxiety since ancient times. The species Passiflora incarnata L. is included in many Pharmacopoeias, and it is the most used species in food, cosmetic, and pharmaceutical industries. However, there are around 600 species of the genus Passiflora and probably other species that can be used safely. Thus, this article was based on a search into the uses of the main species of the genus Passiflora with anxiolytic activity and its main sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 69 publications
0
25
1
1
Order By: Relevance
“…Several species have a long history in traditional herbal therapy, but the medicinal use has been scientifically verified only for very few Passiflora species. In particular, P. incarnata L. is the most widely used top address anxiety disorders in contemporary Western phytotherapy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several species have a long history in traditional herbal therapy, but the medicinal use has been scientifically verified only for very few Passiflora species. In particular, P. incarnata L. is the most widely used top address anxiety disorders in contemporary Western phytotherapy [18].…”
Section: Introductionmentioning
confidence: 99%
“…The most toxic and ubiquitous class 1 elements (Cd, As and Pb), as well as class 2 (Co) and class 3 (Ba, Cr, Cu) must be considered in the risk assessment for all drug products ( USP, 2021 ). The regulatory requirements for the registration of herbal medicines products in Brazil are similar to those in Europe ( da Fonseca et al, 2020 ), however, the limit for heavy metals, metals and metalloids in medicinal plants in natura not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…Passiflora incarnata is a source of alkaloids, phenolic compounds, flavonoid, and cyanogenic glycosides. The primary phytochemicals found in the passionflower are flavonoids (apigenin, luteolin, quercetin, and kaempferol) and flavonoid glycosides (vitexin, isovitexin, orientin, and isoorientin) [ 1 , 2 ]. The species has the highest overall isovitexin content [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic, long-term stress is a pathological condition, which may impair concentration and memory, as well as lead to affective disorders, such as depression, schizophrenia, and the post-traumatic stress disorder [ 7 ]. Passiflora incarnata is one of the herbal remedies used to alleviate the effects of stress [ 2 ]. A rat study demonstrated that long-term use of passionflower was correlated with reduced stress levels and, consequently, increased motivation to act and improved motor activity [ 8 ].…”
Section: Introductionmentioning
confidence: 99%